Combination of Baby Massage and Ear Shenmen to Enhance Infant Sleep Quality: Quasi-Experimental - Maryana, Nana; Noviani, Aris; Yuliarti, Yayu (JURNAL KEBIDANAN, 2025)
One of the determinants of expansion and progression is seen from how well you sleep. According to WHO, in the world babies experience poor sleep quality more than 33%, in Indonesia more than 44%. More than 70% of parents do not consider it a problem at 2022. Non-pharmacological therapies, such as baby massage, Ear Shenmen acupressure to calm down the baby's body to ensure the infant can sleep soundly. The goal was intended to evaluate the combined efficacy of newborn massage and ear shenmen regarding the content of infants' sleep. Design quasi-experimental pre-tests with additional control groups. Baby Nad Kids And Mom's Spa: Population of Infants Aged 3-12 Months. A sample of 36 babies with purposive sampling, divided into 3 groups. The first group is baby massage and ear shenmen, the second group is baby massage and the third group is ear shenmen. Each group was given treatment for 3 weeks with 1 intervention per week, duration of 30 minutes, BISQ instrument with 15 question items. Bivariate data with paired t-test and multivariate with post-hoc bonferroni anova test. The results of infants' sleep quality in the pre test showed the combined vs baby massage value p=0.921, Combined vs Ear Shenmen value p= 1,000, Baby Massage vs Ear Shenmen value p= 0,464, whereas for in the combined group of delta values (124.50), infant massage group (72.80), ear shenmen group (48.50) and confidence value p=0.001 p=(p<0.05). Each group showed an average post value of >200, indicating that all groups were equally effective in raising the caliber of infants' sleep. But, the combined group with a delta value of 124.50 showed a higher increase, Consequently, it may be said that combining infant massage utilizing ear shenmen is more efficacious in enhancing the quality of infants' sleep.